Diagnostic Accuracy of Fine Needle Aspiration Cytology (FNAC) in Metastatic Lymphadenopathy - Baloch, Farhan Abbas; Baloch, Farhan Abbas; Khalid, Ahmareen (International Journal of Pathology, 2018)
Objective: To determine the diagnostic accuracy of Fine needle aspiration cytology (FNAC) in metastaticlymphadenopathy, using histopathology of the same lymph node as a gold standardStudy Design: Cross sectional studySetting: Department of Pathology, Pakistan Institute of Medical Sciences (PIMS), IslamabadDuration of study: Samples were collected from 13th April, 2011 to 09th February, 2013Methodology: After getting adequate clinical data, patients underwent FNAC. The slides were stainedwith Hematoxylin and Eosin (H&E), evaluated according to the set criteria and compared with histopathologicalslidesResults: All of the 54 cases were found to be lymph node lesions. Mean age was 45.17± 17.1 years. Maleto female ratio was 1:1.08. Most of the smears were hypercellular. Most common metastatic tumor wasMetastatic Squamous Cell Carcinoma (51.85%), followed by Metastatic Adenocarcinoma (7.41%). In 38cases, the involved lymph node was found to be cervical, followed by supraclavicular lymph nodewhich was involved in 9 cases. Axillary and inguinal lymph nodes comprised 4 and 3 cases respectively.A strong correlation was found between the diagnosis made by fine needle aspiration cytology andthe final histopathological diagnosis. The sensitivity and specificity of FNAC came out to be 97.37%and 93.75% respectively with an overall diagnostic accuracy of 96.29%.Conclusion: Fine needle aspiration cytology (FNAC) is a useful diagnostic test in metastatic lesions oflymph nodes because it is rapid, simple and inexpensive and has high diagnostic accuracy.